High Activity of N-Acetylcysteine in Combination with Beta-Lactams against Carbapenem-Resistant Klebsiella pneumoniae and Acinetobacter baumannii - Massimiliano De Angelis; Maria T. Mascellino; Maria C. Miele; Dania Al Ismail; Marisa Colone; Annarita Stringaro; Vincenzo Vullo; Mario Venditti; Claudio M. Mastroianni; Alessandra Oliva (MDPI AG, 2022)
Aim: The aim of the study was to evaluate the in vitro activity of N-acetylcysteine (NAC), alone or in combination with beta-lactams, against carbapenem-resistant Klebsiella pneumoniae (CR-Kp) and Acinetobacter baumannii (CR-Ab). Methods: The antibacterial activity of each compound was tested by broth microdilution and the synergism was evaluated by the checkerboard method. Killing studies of NAC alone and in combination with beta-lactams were performed. Bacterial morphological changes were investigated with scanning electron microscopy (SEM). Results: Overall, 30 strains were included (15 CR-Kp and 15 CR-Ab). The NAC Minimal Inhibitory Concentrations (MIC)50/90 were 5/5 and 2.5/5 mg/mL for CR-Kp and CR-Ab, respectively. For both microorganisms, NAC, in addition to beta-lactams (meropenem for CR-Kp, meropenem and ampicillin/sulbactam for CR-Ab, respectively), was able to enhance their activity. The killing studies showed a rapid and concentration-dependent activity of NAC alone; the addition of NAC to meropenem or ampicillin/sulbactam at subinhibitory concentrations induced a fast and lasting bactericidal activity that persisted over time. The SEM analyses showed evident morphological alterations of the bacterial cells following incubation with NAC, alone and in combination with meropenem. Conclusions: NAC demonstrated a high in vitro activity against CR-Kp and CR-Ab and was able to enhance beta-lactams' susceptibility in the tested strains. The preliminary data on the SEM analyses confirmed the in vitro results.